ICT (Instruction Computer Technology) Based PKN and IPS Learning Designs in Elementary Schools - miranda; Yeni Erita; Rena ELIA; Nivetiken (RADINKA JAYA UTAMA PUBLISHER, 2023)
Design is an activity that demands professionalism and competence, because it is impossible for someone to design learning properly and correctly if they do not have the appropriate education and experience. That way, designing requires sufficient knowledge, experience, and observation of the symptoms and characteristics of the problem. The rapid advancement of technology and science has had a major influence on the conditions and circumstances of human life, science and technology have affected the scope of human life, one of which is education, namely the PKN and social studies learning process. The correct implementation of PKN and IPS learning processes is learning activities that increase interest or motivation, as well as student activities in the learning process. ICT-based learning media, namely learning media for all technologies related to retrieval, collection (acquisition), processing, storage, dissemination, and presentation of information/data using computers and telecommunications. ICT is used to support learning processes that are believed to be able to: 1. improve the quality of learning 2. differentiate access to education and learning 3. reduce education costs 4. answer the necessity of participating in ICT, and 5. increase ICT skills (ICT skills) that students need when working in the future Strategies for using ICT in learning include: (1) ICT as a tool or learning media, (2) ICT as a learning facility/place, (3) ICT as a learning resource, and (4) ) ICT as a means of increasing professionalism